Pendidikan Kepramukaan Sebagai Media Pembentukan Karakter Siswa - Mislina, Nuraisyah; Sembiring, Zamalludin (Universitas Muhammadiyah Ponorogo, 2026)
This research aims to analyze scouting education as a medium for student character building by exploring implementation, developed character values, method effectiveness, and supporting and inhibiting factors in organizing scouting programs. The research method uses a qualitative approach with literature review techniques analyzing indexed scientific journals from 2020 to 2025 through content analysis to identify patterns, themes, and consistent findings from various literature sources. The research results show that the implementation of scouting education is carried out systematically through routine training, ceremonial activities, and materials based on Dasa Dharma with methods of habituation, exemplary, assignment, lectures, and educative sanctions. Character values formed include religious dimensions, independence, discipline, responsibility, leadership, honesty, tolerance, mutual cooperation, and environmental care. The effectiveness of scouting methods is demonstrated through learning by doing approaches, educational games, and outdoor activities that create meaningful learning experiences. Supporting factors include principal support, experienced coaches, and adequate facilities, while inhibiting factors include lack of parental support, insufficient student understanding, and time limitations. This research concludes that scouting education effectively shapes students' holistic character through integration of adaptive and innovative scouting methods according to the developmental needs of students in the contemporary era.